Struggle For Autonomy: A Psychoanalytical Study Of Lawrence’s The Stone Angel (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates women's struggle for autotomy through the lens of Freudian psychoanalytic analysis in Stone Angel, with a specific focus on Hagar Shipley's journey towards individuality. Also represented in the novel are gender disparities, their impact on women's empowerment, and the role played by men in upholding societal stability. This paper employs a qualitative approach, focusing on the textual content of The Stone Angel. The primary objective of this study is to dissect the aspects related to Hagar Shipley’s struggle for autonomy, aiming to unveil the complexities of her character and the external influences that shaped her experiences during her pursuit of autonomy. The study examined these intricacies, particularly within the context of patriarchal suppression. This study will serve as a symbol of the intricate interplay between societal norms, unconscious motivations, and the enduring quest for autonomy.